Characteristic of Mandibular Ameloblastoma and Postoperative Complication Influencing Factors in Cipto Mangunkusumo General Hospital during January 2008 – December 2012 - Juliansyah, Amir; Briani, Farida (UI Scholars Hub, 2018)
Introduction. Ameloblastoma is a quite rare case but a common odontogenic tumor found, about 11% of all odontogenic tumors. The tumor is locally aggressive odontogenic one with a tendency to have recurrence and may cause severe facial deformity and dysfunction if not treated properly. The slow growing nature of this tumor usually lead to a delay in diagnostic. Recurrence rate of ameloblastoma reported as 15–25% after radical treatment and 75–90% after conservative treatment. This study aimed to find out the characteristics and influencing factors that contributed to postoperative complication. Method. Those diagnosed as ameloblastoma who underwent total mandibulectomy, hemi–mandibulectomy, segmental mandibulectomy, and subtotal mandibulectomy as the first surgery followed by reconstruction using with reconstruction plate or bone graft in dr. Cipto Mangunkusumo general hospital in during January 2008 – December 2012 were reviewed descriptively using cross sectional retrospective study. Results. Twenty–three subjects managed in the oncology surgery division, Department of Surgery, dr. Cipto Mangunkusumo general hospital during such a period. There were 7 males and 9 females aged in ranged of 20–55–year–old. The majority complained painless swelling (9 subjects, 39.1%) for less than 2 years (12 subjects, 52.2%). The most factor found to be related was tooth extraction (8 subjects, 34.8%), following removal of teeth cyst (6 subjects, 26.1%). The most x–ray finding of panoramic view was multilocular (19 subjects, 82.6%) and the most surgical procedure preceded was partial resection of hemi–mandibulectomy (17 subjects, 73.9%). The most histopathological finding was follicular type (8 subjects (34.8%). Morbidity rate was 21.7%, no mortality. The most complication found was plate exposed (3 subjects, 13.08%). Median length of stay was 9 days (ranged of 7–26 days). There was no recurrence found in this study for 1–year postoperative follow–up. No significance relation between characteristics and complication. Conclusion. The postoperative recurrence rate of mandibular ameloblastoma might be be minimized by a wide excision beyond safety margin.